2022
DOI: 10.1371/journal.pone.0265880
|View full text |Cite
|
Sign up to set email alerts
|

How curriculum delivery translates into entrepreneurial skills: The mediating role of knowledge of information and communication technology

Abstract: This research examines how curriculum delivery predicts entrepreneurial skills, with knowledge of information and communication technology (ICT) as a mediator. Curriculum delivery with the multiple dimensions of objectives, contents, teaching strategies, and feedback and assessment was used in this study, and a quantitative research design was adopted. A questionnaire survey was used to collect data from 482 students at six universities in Lahore, Pakistan, and the partial-least-squares structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…A campus environment that promotes entrepreneurship through experiential learning is shown to have positive outcomes on students' career aspirations and entrepreneurial abilities, through various studies, including those by Barnes and de Villiers Scheepers (2018) and Luo et al (2022). Similarly, Iqbal et al (2022b) conducted a study on students of higher education and found that the curriculum along with the knowledge of ICT enhanced the entrepreneurial competencies among the students. Another study found that the curriculum like curriculum content, material, and teaching strategies enhanced student outcomes, such as ICT competencies (Ashraf et al, 2022).…”
Section: Mediation Effect Of Campus Learning Environmentmentioning
confidence: 99%
“…A campus environment that promotes entrepreneurship through experiential learning is shown to have positive outcomes on students' career aspirations and entrepreneurial abilities, through various studies, including those by Barnes and de Villiers Scheepers (2018) and Luo et al (2022). Similarly, Iqbal et al (2022b) conducted a study on students of higher education and found that the curriculum along with the knowledge of ICT enhanced the entrepreneurial competencies among the students. Another study found that the curriculum like curriculum content, material, and teaching strategies enhanced student outcomes, such as ICT competencies (Ashraf et al, 2022).…”
Section: Mediation Effect Of Campus Learning Environmentmentioning
confidence: 99%
“…Other studies have found similar results. (Iqbal et al, 2022) found no significant effect of formal curriculum delivery on entrepreneurial skills development and performance improvement in Pakistan. Additionally, the metaanalysis of 183 research covering 50,045 enterprises reveals a surprisingly weak correlation between formal education and entrepreneurial performance (Struckell, 2019).…”
Section: Discussionmentioning
confidence: 76%
“…This finding aligns with multiple research studies. The research conducted by (Iqbal et al, 2022) highlights a significant challenge in the advancement of entrepreneurial skills within formal education, thus, the absence of a comprehensive entrepreneurship education curriculum within the formal school system. A study by (Cera et al, 2020) in a Balkan countries demonstrates that the inclusion of entrepreneurship education and practical teachings in formal education curricula increases entrepreneurial intention among students.…”
Section: Discussionmentioning
confidence: 99%
“…Arguing this result, Fahadi et al (2022) indicated the need of knowledge of technology and pedagogy for the successful enhancement of ICT in improvement of education. ICT is useful for entrepreneurship in education (Iqbal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%